(untitled) (Architecture Image Studies, 2026)
Integrating information literacy into Project-Based Learning (PjBL) has become an important educational agenda, yet its implementation remains challenging, particularly at the level of teachers’ instructional planning. This study investigates how Indonesian language teachers conceptualize and plan the integration of information literacy within PjBL, and identifies the pedagogical challenges they encounter in classroom practice. Employing an ethnographic research design, the study was conducted in three junior high schools in Nganjuk, Indonesia. Data were collected through prolonged classroom observations, in-depth interviews with Indonesian language teachers, and analysis of lesson plans and instructional documents. The data were analyzed thematically to capture recurring patterns in teachers’ planning practices and underlying pedagogical assumptions. The findings reveal that teachers tend to interpret information literacy in procedural terms, emphasizing information searching and project completion rather than critical evaluation, synthesis, and ethical use of information. Planning difficulties are further compounded by assessment constraints, limited instructional time, and the absence of explicit curricular guidelines for information literacy integration. As a result, PjBL is often implemented as a product-oriented activity, with limited scaffolding for students’ information-processing and reflective practices. Nevertheless, the study also identifies emerging forms of teacher agency, as educators adapt PjBL through collaborative inquiry and informal reflective activities despite structural constraints. This study contributes to the literature by foregrounding teachers’ lived planning experiences and highlighting the need for conceptually grounded frameworks, aligned assessment strategies, and sustained professional development to support meaningful integration of information literacy within PjBL in secondary education contexts.